Cdk1 Activity Is Required for Mitotic Activation of Aurora A during G(2)/M Transition of Human Cells - Van Horn, Robert D. (American Society for Biochemistry and Molecular Biology, 2010)
In mammalian cells entry into and progression through mitosis are regulated by multiple mitotic kinases. How mitotic kinases interact with each other and coordinately regulate mitosis remains to be fully understood. Here we employed a chemical biology approach using selective small molecule kinase inhibitors to dissect the relationship between Cdk1 and Aurora A kinases during G(2)/M transition. We find that activation of Aurora A first occurs at centrosomes at late G(2) and is required for centrosome separation independently of Cdk1 activity. Upon entry into mitosis, Aurora A then becomes fully activated downstream of Cdk1 activation. Inactivation of Aurora A or Plk1 individually during a synchronized cell cycle shows no significant effect on Cdk1 activation and entry into mitosis. However, simultaneous inactivation of both Aurora A and Plk1 markedly delays Cdk1 activation and entry into mitosis, suggesting that Aurora A and Plk1 have redundant functions in the feedback activation of Cdk1. Together, our data suggest that Cdk1, Aurora A, and Plk1 mitotic kinases participate in a feedback activation loop and that activation of Cdk1 initiates the feedback loop activity, leading to rapid and timely entry into mitosis in human cells. In addition, live cell imaging reveals that the nuclear cycle of cells becomes uncoupled from cytokinesis upon inactivation of both Aurora A and Aurora B kinases and continues to oscillate in a Cdk1-dependent manner in the absence of cytokinesis, resulting in multinucleated, polyploidy cells.